DOMINANT FACTORS RELATED TO USE OF MALE CONDOMS OF MAN WHO HAVE SEX WITH MEN IN BULELENG REGENCY - Megaputri, Putu Sukma; Sedana, Ketut Putra; Widiarta, Made Bayu Oka (Universitas Muhammadiyah Malang, 2019)
Men who have sex with men(MSM) community had become one of the epicentrum of transmission of STIs and HIV / AIDS. The results of an integrated survey of biological behavior of MSM condom use are only less than 50%. The objective of this study is to determine the most dominant factors increasing condom use in MSM. Survey Cross sectional study on MSM with a sample of 58 people selected by snowball sampling when MSM examined the Buleleng Health Center 1. Data collection was done by interviewing a questionnaire related to: social demographic characteristics, internal, external factors, negotiation and condom use. Data were analyzed by chi square followed by logistic regression using software. The study found that several factors related to condom use in MSM namely marital status showed that the respondents were unmarried (AOR: 9.5, 96% CI 1.5-59.7). Then the perception of high MSM susceptibility was also related to condom use (AOR: 6.5, 96% CI 1.3-33.3). Subsequently the availability of condoms on site and carried by MSM (AOR: 6.8, 96% CI 1.1-45.6). Factors related to condom use in MSM in Buleleng Regency are unmarried status, condom availability and perceived susceptibility.